2013
DOI: 10.1073/pnas.1302159110
|View full text |Cite
|
Sign up to set email alerts
|

Learning-induced neural plasticity of speech processing before birth

Abstract: Learning, the foundation of adaptive and intelligent behavior, is based on plastic changes in neural assemblies, reflected by the modulation of electric brain responses. In infancy, auditory learning implicates the formation and strengthening of neural long-term memory traces, improving discrimination skills, in particular those forming the prerequisites for speech perception and understanding. Although previous behavioral observations show that newborns react differentially to unfamiliar sounds vs. familiar s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
160
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(170 citation statements)
references
References 53 publications
5
160
1
4
Order By: Relevance
“…Research shows that children are sensitive to language even prenatally (Moon et al, 2013;Partanen et al, 2013), yet in the first few months after a child is born, general language experiences are more likely to make a difference than reading aloud. However, as no negative effects of a very early start of reading to a child are to be expected, the sooner the better appears to be best.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows that children are sensitive to language even prenatally (Moon et al, 2013;Partanen et al, 2013), yet in the first few months after a child is born, general language experiences are more likely to make a difference than reading aloud. However, as no negative effects of a very early start of reading to a child are to be expected, the sooner the better appears to be best.…”
Section: Discussionmentioning
confidence: 99%
“…Children's language and literacy competence does not begin when children enter school-Children's literacy learning starts well before formal schooling, and studies have shown that children are sensitive to speech even prenatally (e.g., Moon, Lagercrantz, & Kuhl, 2013;Partanen et al, 2013). Parents and primary caregivers (subsequently referred to as parents) are highly influential in a child's early learning as parent-child interactions are frequent and ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Beauchemin et al have found activation in language-related cortical regions when newborns listened to their mother's voice, whereas a stranger's voice seemed to activate more generic regions of the brain (20). In addition, Partanen et al have shown that the neural response to maternal sounds depends on experience as full-term newborns react differentially to familiar vs. unfamiliar sounds they were exposed to as fetuses, suggesting correlation between the amount of prenatal exposure and brain activity (21). Taken together, the above studies suggest that the mother's voice plays a special role in the early shaping of auditory and language areas of the brain.…”
mentioning
confidence: 99%
“…Developmental studies in the language domain have uncovered basic perceptual (4-6), discrimination (7,8), and mnemonic capacities (9)(10)(11)(12)(13)(14) in newborns and fetuses, supporting the hypothesis that memories for sounds begin to be established very early in life. However, infants' memory for specific words seems to be highly vulnerable to interference.…”
mentioning
confidence: 88%